Migration to Sweden from the new EU member states - Eskil Wadensjö (Institute for the Study of Labor (IZA), 2007)
Sweden did not apply any transitional rules for migrants coming from the ten new European Union member states in May 2004. The migration to Sweden from these countries also increased, especially from Poland and the Baltic states, even if not to the same extent as the immigration to Ireland and the UK (two countries with transitory rules of minor importance). The composition of the migrants changed. While earlier many more women than men arrived, now the gender composition is much more even. In this paper the labour market situation is studied for people living in Sweden at the end of 2005 who were either born in one of new member states or born in Sweden. The immigrants are represented in all sectors of the economy but overrepresented in some sectors. Their wages controlling for education are somewhat lower than those for natives. The labour market situation is rather good for the new immigrants and they are not overrepresented in different income transfer programs. The knowledge of these conditions may explain that Sweden abstained from introducing transitional rules also when Bulgaria and Romania became members of the European Union in January 2007.
Keywords: J61; 330; International migration; migration policy; common labour market; Einwanderung; Osteuropäer; Arbeitsmarkt; Einwanderungsrecht; Schweden